Sosialisasi Bahasa Anti-Perundungan di Lingkungan Sekolah - Eka, Eka Septiani; Nur Indah Sari; Eva Yuni Rahmawati (Universitas Pamulang, 2025)
The rapid development of technology today has brought about many new challenges, one of which is the rise of cyberbullying and bullying behavior. Cases of cyberbullying or bullying can also occur within the school environment, fueled by the various forms of social media available. Students can easily access and use their social media accounts. Unfortunately, many of them have not yet learned how to use technology wisely. Being wise in using social media means understanding the language used in bullying behavior at school, as well as knowing how to prevent such behavior from occurring. An anti-bullying language awareness program was held at SMAN 16 Bekasi, involving 30 students. The program included both a pre-test and a post-test for participants. The main goal was to provide counseling and guidance to help students minimize or prevent incidents of cyberbullying or bullying within the school environment. To put this attitude into practice, a sustainable educational program is needed through continuous outreach activities. The planned follow-up mentoring sessions are expected to help students develop a better understanding of language use—particularly in preventing cyberbullying.